Educational data mining towards knowledge engineering: a review state. (2016) - Sukhija, Karan; Jindal, Manish; Aggarwal, Naveen
Data mining extracts the information from an enormous data provisions, often recognised as knowledge discovery in databases. It is procedure of semi-automatically examining huge amount of databases to discover valuable patterns. Knowledge management is a multifaceted approach that assists in attaining executive objectives by building the pre-eminent use of knowledge. This paper has threefold objective. Initially, it explains data mining process and numerous data mining techniques that help in the removal of concealed patterns. Furthermore, it elaborates the numerous tendencies and fields amended data mining technology for easy access and reclamation of valuable information. Data mining application area comprises marketing, telecommunication deception, funding, medicinal education area and so on. At last, emphases on educational data mining that is related with emerging techniques to explore the distinguished data gained from educational settings and consequences in dropping the intricacy of numerous data mining tools used by educationalists is given.